A Retrospective Study on the Eye-Related Quality of Life, Functional Vision, and Their Determinants Among Children Following Congenital and Developmental Cataracts Surgery and Its Impact on Their Families Using the PedEyeQ - Siyi Gu; Siyi Gu; Siyi Gu; Yiwen Hu; Yiwen Hu; Yiwen Hu; Yinying Zhao; Yinying Zhao; Yinying Zhao; Lulu Chen; Lulu Chen; Lulu Chen; et al. (Frontiers Media S.A., 2022)
ObjectivesTo evaluate the eye-related quality of life (ER-QOL), functional vision, and their determinants in children following congenital and developmental cataract surgery, as the impact on their families, using the Pediatric Eye Questionnaire (PedEyeQ).Materials and MethodsThis was a retrospective cross-sectional study involving 107 children (aged 0-11 years) with congenital and developmental cataracts who had undergone surgery, as well as 59 visually healthy controls (aged 0-11 years). One parent for each child completed either the Proxy 0-4 PedEyeQ, the Proxy 5-11 PedEyeQ, or the Parent PedEyeQ, depending on their child's age. Mann-Whitney U and Kruskal-Wallis tests were then conducted to compare the differences between groups and to analyze their determinants.ResultsPedEyeQ scores were found to be lower in postoperative children with congenital and developmental cataracts compared with the control group across all study domains. The PedEyeQ Proxy 0 to 4 years' greatest mean difference was 27 points worse in the Functional Vision domain (95% CI −34 to −19; p < 0.001). We also found that the occurrence of nystagmus (p < 0.005) and strabismus (p < 0.005) were the major factors affecting participants' functional vision. The PedEyeQ Proxy 5 to 11 years' greatest mean difference was 23 points worse in this same domain (95% CI −30 to −15; p < 0.001), with nystagmus (p < 0.05) being the main determinant herein. Parent PedEyeQ 0 to 4 years' greatest difference was 46 points worse on the Worry about their Child's Eye Condition domain (95% CI −57 to −36; p < 0.001). Similarly, parents of children with ophthalmologic abnormalities, including nystagmus (p < 0.001) and strabismus (p < 0.05), were significantly more worried about their children's eye condition. Parent PedEyeQ 5 to 11 years' greatest difference was also found to be 30 points worse on the Worry about their Child's Eye Condition domain (95% CI −43 to −17; p < 0.005).ConclusionsChildren who have undergone congenital and developmental cataract surgery experience a lower quality of life and reduced functional vision. Their families are also significantly and adversely affected herein. Thus, more attention is needed on these groups, with more focused measures being administered to both children and their families.